The effect of rearing temperature in larval development of pejerrey, Odontesthes bonariensis- Morphological indicators of development - Chalde, Tomás (2011)
It is well known that in pejerrey water temperature not only affects growth rates but also directs the sexual differentiation process. This fact rise the question of how different the development of pejerrey larvae of the same age is when reared at different temperatures. A description of developmental stages for the embryonic and larval periods of the pejerrey, Odontesthes bonariensis, and the influence of rearing temperature on larval development are presented. Then, larval development was studied at three rearing temperatures, and changes in general morphology, fin morphology, and caudal fin structure have been taken into consideration within the thermal range involved in the temperature sex determination of this species. Fin fold reabsorption, caudal fin formation, and body shape were selected to follow the events leading to the acquisition of the juvenile morphology. The juvenile phenotype was defined when the fin fold was reabsorpted and the caudal fin acquired its definitive homocercal structure. The moment at which the juvenile phenotype was achieved, was evaluated in relation to larval age, size and, shape. The size resulted as the best indicator of development in pejerrey.